Dear Blue Sky - Sullivan, Mary, 1966- (Nancy Paulsen Books, 2012)
"Shortly after Cass's big brother is deployed to fight in Iraq, Cass becomes pen pals with an Iraqi girl who opens up her eyes to the effects of war"--